Implikasi dan Akibat Hukum Putusan Mahkamah Konstitusi Nomor 69/Puu-Xiii/2015 terhadap Pembuatan Akta Perjanjian Perkawinan Setelah Kawin yang Dibuat di Hadapan Notaris - Eva Dwinopianti (Lex Renaissance, 2017)
AbstractThis study aims to determine the implications of the Constitutional Court Decision No. 69 / PUU-XII / 2015 and the legal consequences for making the marriage contract after the Constitutional Court ruling on the status of property and third parties who feel aggrieved over the agreement. This study is a normative by using approaches Act (statuteapproach) and the conceptual approach (conseptualapproach).The data used is secondary data in the form of primary legal materials, secondary and tertiary. The results showed that the implications of the Constitutional Court Decision No. 69 / PUU-XIII / 2015 against the deed covenant marriage after the wedding before a Notary change the legal mechanism of making the marriage contract that can now be created during the marriage bond takes place by the Notary without preceded by court decision authorized. While the legal consequences of the marriage covenant deed after mating before the Constitutional Court ruling that the changes to the property status of husband and wife and binding upon both parties and against third parties. Later than it was after the Constitutional Court the legal consequences of making the marriage contract after the wedding on the status of joint property inherent (closely related) to the time of entry into force of  the agreement and binding on third parties.Keywords: Marital agreement, the notary, the constitutional court's decision